Development and Validation of the Economic Coercion Scale 36 (ECS-36) in Rural Bangladesh - Yount, Kathryn M. (Journal of interpersonal violence, 2022)
Assessing progress toward Sustainable Development Goal (SDG) 5, to achieve gender equality and to empower women, requires monitoring trends in intimate partner violence (IPV). Current measures of IPV may miss women?s experiences of economic coercion, or interference with the acquisition, use, and maintenance of financial resources. This sequential, mixed-methods study developed and validated a scale for economic coercion in married women in rural Bangladesh, where women?s expanding economic opportunities may elevate the risks of economic coercion and other IPV. Forty items capturing lifetime and prior-year economic coercion were adapted from formative qualitative research and prior scales and administered to a probability sample of 930 married women 16?49 years. An economic coercion scale (ECS) was validated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) with primary data from random-split samples (N1 = 310; N2 = 620). Item response theory (IRT) methods gauged the measurement precision of items and scales over the range of the economic-coercion latent trait. Multiple-group factor analysis assessed measurement invariance of the economic-coercion construct. Two-thirds (62.26%) of women reported any lifetime economic coercion. EFA suggested a 36-item, two-factor model capturing barriers to acquire and to use or maintain economic resources. CFA, multiple group factor analysis, and multidimensional IRT methods confirmed that this model provided a reasonable fit to the data. IRT analysis showed that each dimension provided most precision over the higher range of the economic coercion trait. The Economic Coercion Scale 36 (ECS-36) should be validated elsewhere and over time. It may be added to violence-specific surveys and evaluations of violence-prevention and economic-empowerment programs that have a primary interest measuring economic coercion. Short-form versions of the ECS may be developed for multipurpose surveys and program monitoring.